2018
DOI: 10.1186/s12888-018-1818-4
|View full text |Cite
|
Sign up to set email alerts
|

Community-based rehabilitation intervention for people with schizophrenia in Ethiopia (RISE): a 12 month mixed methods pilot study

Abstract: BackgroundCommunity-based rehabilitation (CBR), or community-based inclusive development, is an approach to address the complex health, social and economic needs of people with schizophrenia in low and middle-income countries. Formative work was undertaken previously to design a culturally appropriate CBR intervention for people with schizophrenia in Ethiopia. The current study explored the acceptability and feasibility of CBR in practice, as well as how CBR may improve functioning among people with schizophre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
150
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(157 citation statements)
references
References 38 publications
5
150
0
2
Order By: Relevance
“…Sixteen of the included papers described the integrated recovery services model used to achieve recovery for adults with severe mental illness ( Table 3). Most of the papers suggested that integrated recovery service model can be delivered through illness management (38)(39)(40)(41)(42)(43)(44), mindfulness-based interventions (45), task-sharing or shifting approach (25,26), home visits concept (29,46,47), active leisure or recreational activities (32,37) and music therapy (27) (see Table 4). The reviewed papers highlighted that the integrated recovery services generally aim at developing independent living skills, improve quality of life, community mobilisation (39), reducing inpatient and crisis services, adhering to treatment and setting meaningful goals towards recovery (40,41,46).…”
Section: Philosophy Of Recovery Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen of the included papers described the integrated recovery services model used to achieve recovery for adults with severe mental illness ( Table 3). Most of the papers suggested that integrated recovery service model can be delivered through illness management (38)(39)(40)(41)(42)(43)(44), mindfulness-based interventions (45), task-sharing or shifting approach (25,26), home visits concept (29,46,47), active leisure or recreational activities (32,37) and music therapy (27) (see Table 4). The reviewed papers highlighted that the integrated recovery services generally aim at developing independent living skills, improve quality of life, community mobilisation (39), reducing inpatient and crisis services, adhering to treatment and setting meaningful goals towards recovery (40,41,46).…”
Section: Philosophy Of Recovery Servicesmentioning
confidence: 99%
“…Conversely, music-creation therapy used as recovery services were run for 32 weekly sessions, with a duration of 90 min for each session (27). Generally, the activities of recovery service model covers components such as cognitive behaviour therapy techniques, psychoeducation, relapse prevention, social and coping skills training (meals, guidance in activities of daily living, role-playing, hobby groups) (38,40,46), adherence support, family therapy, crisis management, household contribution and understanding medication (25,29,46). More speci cally, Tjornstrand, Bejerholm (37) recommended that active leisure implemented as recovery services can take several activities, including playing sports, the opportunity to play games, eat, and socialize, embarking on excursions and relaxation (see Table 4).…”
Section: Philosophy Of Recovery Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired psychosocial functioning in patients with SMI is multifactorial: adverse medication reactions (parkinsonism, obesity), and treatment setting (in-or outpatient) may influence functional recovery (9)(10)(11)(12)(13). For example, the medication side effect parkinsonism is associated with poor vocational performance (11), while some studies show positive results for community-based rehabilitation versus in-hospital treatment in patients with SMI (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Günlük işlevsellik düzeyi ve yaşam kalitesi düşüktür. [1,2] Hastaların sağlıklı yaşam davranışları edinmesi ve sürdürmesi zordur, fiziksel sağlık sorunları sık görülür, ayrıca tedavide kullanılan psikotrop ilaçların yan etkileri hastaların yaşamına yeni sorunlar ekleyebilir. [3,4] Dolayısı ile rehabilitasyon programında kronik ruhsal hastaların sağlığı biyopsikososyal açıdan bütüncül olarak ele alınmalıdır.…”
unclassified